Comparison of Capital Structure Between Multinational and Domestic Company in The Fast-Moving Consumer Goods Sector For The Period 2020-2022 - Drunart, Erlangga; Nauli, Intan (Universitas Mercu Buana, 2024)
This study aims to analyze the capital structure and capital budgeting of two companies, namely UNVR and INDF, in the context of investment decisions during the period 2020-2022. The analysis methods used include normality tests, homogeneity tests, and t-tests to compare financial variables, namely Debt to Equity Ratio (DER), Debt Ratio (DR), Equity Ratio (ER), and Dividend Yield (DY). The normality test results show that all variables are normally distributed. The homogeneity test indicates that the variances between groups are homogeneous. The t-test results indicate that there are significant differences between the DER, DR, and ER of the two companies, with UNVR having higher DER and DR, while INDF has a better ER. However, there is no significant difference for DY, despite INDF's higher dividend yield. These findings offer substantial assistance to investors in considering investment decisions based on the capital structure and dividend policies of both companies.